Reversible adhesion polyelectrolyte electronic interface material and preparation method thereof
By combining polyamphora electrolyte networks and grafting amino functional groups in bioelectronic interface materials, the problems of weakening adhesion and interface fatigue on uneven cardiac tissue are solved, and high mechanical adaptability and reversibility are achieved Adhesion and fatigue resistance.
Patent Information
- Application Number
- CN202411583724.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-07
AI Technical Summary
Existing bioelectronic interface materials have problems of weakening adhesion, interface fatigue and mechanical and electrical faults on uneven cardiac tissue, which is difficult to meet the needs of high adhesion, non-invasive separation, anti-swelling and fatigue resistance.
Reversible adhesion polyelectrolyte electronic interface material is used, and a hydrogel network with polyamphora electrolyte network and grafted amino functional groups are combined to form materials with high mechanical and tissue adaptability, reversible adhesion, swelling and fatigue resistance.
High adhesion, non-invasive separation, anti-swelling and fatigue resistance on uneven tissue interfaces are achieved, and the stability and reliability of bioelectronic interface materials are improved.
Smart Images

Figure HDA0005123791850000011 
Figure HDA0005123791850000012 
Figure HDA0005123791850000013
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of biomaterials, and more specifically, relates to a reversible adhesion polyelectrolyte electronic interface material (BPAIE) and a preparation method thereof. Background Art
[0002] Bioadhesives can be used to create robust bioelectronic tissue interfaces for electrophysiological monitoring and diagnosis of various diseases. Recently, integration of bioelectronic interface materials with cardiac tissue has emerged as a promising approach to provide epicardial electrocardiogram (ECG).
[0003] However, there are still some problems in the current research:
[0004] On the one hand, natural biopolymers form wet adhesion by forming different types of physical interactions with tissues (hydrogen bonding, π-π interactions, electrostatic interactions, and coordination); however, the physical adhesion of these adhesives weakens over time when a hydrated layer forms on the tissue surface.
[0005] On the other hand, adhesives with strong adhesion mainly form strong amide covalent bonds with tissue surfaces through AAc and acrylate-N-hydroxysuccinimide ester (AAc-NHS), which can cause excessive swelling due to the large number of carboxyl groups in the polymer network.
[0006] Finally, when targeting heterogeneous cardiac tissue, especially under the dynamic cardiac systole-diastole cycle, interface fatigue may lead to mechanical and electrical failure of flexible devices.
[0007] Therefore, there is an urgent need to develop a bioelectronic interface material that is suitable for heterogeneous tissue interfaces and has properties such as high adhesion, non-invasive separation, anti-swelling, and anti-fatigue. Summary of the invention
[0008] The object of the present invention is to provide a bioelectronic interface material which is suitable for uneven tissue interfaces and has the properties of high adhesion, non-invasive separation, anti-swelling, anti-fatigue and the like.
[0009] In a first aspect of the present invention, a reversible adhesion polyelectrolyte electronic interface material is provided, the material comprising the following components:
[0010] (a) a polyampholyte network, wherein the polyampholyte network comprises an anionic monomer NaSS and a cationic monomer DMAEA-Q;
[0011] (b) A hydrogel network grafted with amino functional groups, wherein the hydrogel network is polymerized from amino functional monomers and has a structural formula of XSS-NH 2 ,
[0012] Among them, X is a hydrophilic hydrogel monomer, -SS- is a disulfide bond, -NH 2 is an amino functional group; and
[0013] (c) Metal coating.
[0014] In another preferred embodiment, (a) network and (b) network are interpenetrating networks.
[0015] In another preferred embodiment, (a) network and (b) network together form a bonding base.
[0016] In another preferred embodiment, (a) and (b) are mixed in the form of precursor solutions to obtain a mixed solution, and the mixed solution is polymerized by ultraviolet light to form an adhesive substrate having a solid network structure.
[0017] In another preferred embodiment, in the adhesive substrate, the proportion of (b) is 0.1wt%-10wt%, preferably 0.5wt%-2wt%.
[0018] In another preferred embodiment, the upper surface of the adhesive substrate is attached with electrodes and wires, and the lower surface is adhered to biological tissue.
[0019] In another preferred embodiment, the metal coating is used to prepare an electrode.
[0020] In another preferred example, the metal coating includes a conductive gallium-indium (EGaIn) liquid metal coating and / or a gold coating.
[0021] In another preferred embodiment, the metal coating is used to prepare a conductive material attached to the surface of a bonding substrate.
[0022] In another preferred example, the conductive material further includes a conductive polymer coating.
[0023] In another preferred embodiment, the polyampholyte network is hydrophobic.
[0024] In another preferred embodiment, the polyampholyte network is a controlled swelling network.
[0025] In another preferred embodiment, the molar ratio of the anionic monomer NaSS to the cationic monomer DMAEA-Q is 1:0.75-1:1.5.
[0026] In another preferred embodiment, the polyampholyte network produces a swelling effect in a salt solution.
[0027] In another preferred embodiment, the polyampholyte network produces a shrinkage effect in a non-salt solution.
[0028] In another preferred embodiment, the hydrogel network grafted with amino functional groups has reversible adhesion.
[0029] In another preferred embodiment, the hydrogel network grafted with amino functional groups is connected via -NH 2 Adhere to the surface of biological tissue.
[0030] In another preferred embodiment, the hydrogel network grafted with amino functional groups can break disulfide bonds in the presence of a separation solution, thereby non-invasively detaching from the surface of biological tissues.
[0031] In another preferred example, the separation solution is a solution containing sodium chloride and glutathione.
[0032] In another preferred example, the sodium chloride is used to break down the physical crosslinks between the biological tissue and the adhesive substrate, and the physical crosslinks are connected through carboxylate groups.
[0033] In another preferred embodiment, the glutathione is used to break down the covalent cross-links between biological tissues and adhesive substrates, and the covalent cross-links are connected via disulfide bonds.
[0034] In another preferred embodiment, the hydrophilic hydrogel includes hyaluronic acid hydrogel, gelatin hydrogel and polysaccharide hydrogel.
[0035] In another preferred embodiment, the reversibly adhesive polyelectrolyte electronic interface material has the following characteristics: high mechanical and tissue adaptability, reversible adhesion, anti-swelling, anti-fatigue, biocompatibility, conductivity, or a combination thereof.
[0036] The second aspect of the present invention provides a reversibly adhesive polyelectrolyte hydrogel, the hydrogel comprising the following components:
[0037] (a) a polyampholyte network, wherein the polyampholyte network comprises an anionic monomer NaSS and a cationic monomer DMAEA-Q; and
[0038] (b) A hydrogel network grafted with amino functional groups, wherein the hydrogel network is polymerized from amino functional monomers and has a structural formula of XSS-NH 2 ,
[0039] Among them, X is a hydrophilic hydrogel monomer, -SS- is a disulfide bond, -NH 2 It is an amino functional group.
[0040] In another preferred embodiment, (a) network and (b) network are interpenetrating networks.
[0041] In another preferred embodiment, (a) network and (b) network together form a bonding base.
[0042] In another preferred embodiment, (a) and (b) are mixed in the form of precursor solutions to obtain a mixed solution, and the mixed solution is polymerized by ultraviolet light to form an adhesive substrate having a solid network structure.
[0043] In another preferred embodiment, in the adhesive substrate, the proportion of (b) in the adhesive substrate is 0.1wt%-10wt%, preferably 0.5wt%-2wt%.
[0044] In another preferred embodiment, the polyampholyte network is hydrophobic.
[0045] In another preferred embodiment, the molar ratio of the anionic monomer NaSS to the cationic monomer DMAEA-Q is 1:0.75-1:1.5.
[0046] In another preferred embodiment, the polyampholyte network is a controlled swelling network.
[0047] In another preferred embodiment, the polyampholyte network produces a swelling effect in a salt solution.
[0048] In another preferred embodiment, the polyampholyte network produces a shrinkage effect in a non-salt solution.
[0049] In another preferred embodiment, the hydrogel network grafted with amino functional groups has reversible adhesion.
[0050] In another preferred embodiment, the hydrogel network grafted with amino functional groups is connected via -NH 2 Adhere to the surface of biological tissue.
[0051] In another preferred embodiment, the hydrogel network grafted with amino functional groups can break disulfide bonds in the presence of a separation solution, thereby non-invasively detaching from the surface of biological tissues.
[0052] In another preferred example, the separation solution is a solution containing sodium chloride and glutathione.
[0053] In another preferred example, the sodium chloride is used to break down the physical crosslinks between the biological tissue and the adhesive substrate, and the physical crosslinks are connected through carboxylate groups.
[0054] In another preferred embodiment, the glutathione is used to break down the covalent cross-links between biological tissues and adhesive substrates, and the covalent cross-links are connected via disulfide bonds.
[0055] In another preferred embodiment, the hydrophilic hydrogel includes hyaluronic acid hydrogel, gelatin hydrogel and polysaccharide hydrogel.
[0056] In another preferred embodiment, the hydrogel is used to load small molecule drugs, nucleic acid drugs, polypeptide drugs, or a combination thereof.
[0057] In another preferred embodiment, the hydrogel is used for drug delivery in vitro or in vivo tissues.
[0058] In another preferred embodiment, the in vitro tissue or in vivo tissue includes heart tissue, intestinal lining, skin tissue, and muscle tissue.
[0059] In a third aspect of the present invention, a reversible adhesion hydrogel is provided, wherein the hydrogel is a network structure formed by polymerization of amino-functionalized monomers, wherein the structural formula of the monomers is XSS-NH 2 ,
[0060] Among them, X is a hydrophilic hydrogel monomer, -SS- is a disulfide bond, -NH 2 It is an amino functional group.
[0061] In another preferred embodiment, the hydrogel has reversible adhesion.
[0062] In another preferred embodiment, the hydrogel is 2 Adhere to the surface of biological tissue.
[0063] In another preferred embodiment, the hydrogel is non-traumatically peeled off from the tissue surface in the presence of a separation solution.
[0064] In another preferred example, the separation solution is a solution containing sodium chloride and glutathione.
[0065] In another preferred embodiment, the sodium chloride is used to lyse the physical crosslinks between biological tissue and hydrogel, and the physical crosslinks are connected through carboxylate groups.
[0066] In another preferred embodiment, the glutathione is used to cleave the covalent cross-links between biological tissue and hydrogel, and the covalent cross-links are connected via disulfide bonds.
[0067] In another preferred embodiment, the hydrophilic hydrogel includes hyaluronic acid hydrogel, gelatin hydrogel and polysaccharide hydrogel.
[0068] In another preferred embodiment, the hydrogel is used to load small molecule drugs, nucleic acid drugs, polypeptide drugs, or a combination thereof.
[0069] In another preferred embodiment, the hydrogel is used for drug delivery in vitro or in vivo tissues.
[0070] In another preferred embodiment, the in vitro tissue or in vivo tissue includes heart tissue, intestinal lining, skin tissue, and muscle tissue.
[0071] A fourth aspect of the present invention provides a method for preparing a reversibly adhesive biomaterial, the method comprising the following steps:
[0072] (a) Preparation of a hydrogel monomer solution grafted with amino functional groups, the structural formula of which is XSS-NH 2 ,
[0073] Among them, X is a hydrophilic hydrogel monomer, -SS- is a disulfide bond, -NH 2 is an amino functional group;
[0074] (b) preparing a polyampholyte solution;
[0075] (c) (a) and (b) are mixed to obtain a reversibly adhesive biomaterial.
[0076] In another preferred embodiment, a conductive material is added to the reversibly adhesive biomaterial to form an electronic interface material for detecting electrical signals of biological tissues.
[0077] In another preferred embodiment, the conductive material includes liquid metal coating, gold coating, and conductive polymer coating.
[0078] In another preferred embodiment, the method further comprises: printing gallium-indium liquid metal on the surface of the reversibly adhesive biomaterial.
[0079] In another preferred embodiment, the step (a) comprises: mixing and dissolving hyaluronic acid, N-hydroxysuccinimide (ZHS) and EDC to obtain a hydrogel monomer solution grafted with amino functional groups.
[0080] In another preferred embodiment, the step (b) comprises: mixing anionic monomer NaSS and cationic monomer DMAEA-Q to obtain a polyampholyte solution.
[0081] In another preferred embodiment, the step (c) further comprises: (a) and (b) are mixed in the form of a solution to obtain a mixed solution, and the mixed solution is polymerized by ultraviolet light to form a solid reversible adhesion biomaterial.
[0082] In another preferred embodiment, in the reversible adhesion biomaterial, the proportion of (b) is 0.1wt%-10wt%, preferably 0.5wt%-2wt%.
[0083] A fifth aspect of the present invention provides a use of a reversibly adhesive polyelectrolyte electronic interface material for detecting electrical signals on the surface of uneven biological tissues.
[0084] In another preferred embodiment, the heterogeneous biological tissue includes: heart tissue, intestinal lining, and muscle.
[0085] In another preferred embodiment, the reversibly adhesive polyelectrolyte electronic interface material is used to detect epicardial electrical signals.
[0086] It should be understood that within the scope of the present invention, the above-mentioned technical features of the present invention and the technical features specifically described below (such as embodiments) can be combined with each other to form a new or preferred technical solution. Due to space limitations, they will not be described one by one here. BRIEF DESCRIPTION OF THE DRAWINGS
[0087] Figure 1 Shown are the chemical structure of the cationic monomer (DMAEA-Q); the chemical structure of the anionic monomer (NaSS); and the chemical structure of the amino-functionalized hyaluronic acid monomer HA-Cys.
[0088] Figure 2 BPA is shown to have high mechanical and tissue adaptability during dynamic cardiovascular dilation and contraction: anti-swelling process of BPA network (i-ii); (ii-iv) stretching and recovery process of BPA network.
[0089] Figure 3 The synthetic NMR spectrum of amino-functionalized hyaluronic acid is shown.
[0090] Figure 4 Shown are: (a) water content of four types of bioadhesive polyelectrolyte hydrogels measured gravimetrically over time during swelling experiments; (b) scanning electron microscopy images of sample 1 and sample 3 in the freeze-dried state.
[0091] Figure 5 Shown: Cyclic loading-unloading tensile test of sample 1.
[0092] Figure 6 Shown are: stress-displacement curves (a) and fracture energy comparison diagram (b) for sample 1 (blue) and sample 3 (red) and notch curves (light-colored lines) used to evaluate the fracture energy.
[0093] Figure 7 Shown are: (a) the change in resistance of sample 1 / liquid metal composite with strain. (b) the resistance durability of sample 1 / liquid metal composite under 0% and 30% repeated strains and 1000 cycles at a speed of 50 mm / min.
[0094] Figure 8Shown are: (a) interface toughness and displacement curves of four bioadhesive polymer samples 1, 2, 3, and 4 in a 180° peel test on porcine heart tissue; (b) lap shear stress and displacement curves of lap shear test on porcine heart tissue; (c) tensile stress and displacement curves of polymer tensile test on porcine heart tissue of samples 1, 2, 3, and 4; (d) interface toughness, lap shear strength, and tensile strength of adhesion between porcine heart tissue and samples 1, 2, 3, and 4; (e) robust adhesion of sample 1 on the heart in vivo and separation process; (f) Fluorescence microscopy images of BPA hydrogels with and without amine groups: (i) Sample 1 hydrogel without HA-Cys; (ii) Initial state sample 1; (iii) State after immersion in PBS solution with 0.5 M sodium chloride for 5 min; (iv) State after immersion in PBS containing separation solution for 5 min; (g) Schematic diagram of triggerable separation verification based on fluorescent carboxylic acid-coupled fluorophores; (h) Effect of separation solution on interfacial toughness; (i) Characterization of adhesive hydrogels by UV-visible absorption spectroscopy. Dynamic SS bonds are formed in the sample 1 film (blue curve), dynamic bonds are maintained after incubation in 0.5 M sodium chloride (yellow curve), dynamic bonds in the separation solution are cleaved (red curve), and adhesive hydrogels without dynamic bonds (green curve).
[0095] Fig. 9 The cell compatibility of the BPAIE group, acrylic acid-based hydrogel group, and blank group without any implantation is shown: (a) LIVE / DEAD staining images of L929 cells after 24 hours of culture in the presence of material extracts. (b) L929 cell viability on days 1, 4, and 7 after culture in the presence of material extracts based on CCK-8 assay.
[0096] Fig.10 The fabrication process of the BPAIE electrode is shown.
[0097] Fig.11 The in vivo test of cardiac signal recording in a rat heart and the schematic diagram and signals of the BPAIE four-channel electrocardiogram are shown. DETAILED DESCRIPTION
[0098] After extensive and in-depth research, the inventors have developed a reversible adhesion polyelectrolyte electronic interface material (BPAIE) and its preparation method. By combining the anti-fatigue and anti-swelling polyampholyte (PA) network and the grafted amino functional group (-NH 2 ) hyaluronic acid (HA) network and conductive gallium-indium (EGaIn) liquid metal coating, the BPAIE of the present invention has high mechanical and tissue adaptability, reversible adhesion, anti-swelling, anti-fatigue, conductivity and other characteristics, and can be used for accurate monitoring of electrical signals at uneven tissue interfaces such as epicardium. On this basis, the present invention was completed.
[0099] the term
[0100] In order to make the present invention more easily understood, some technical and scientific terms are specifically defined below. Unless otherwise specifically defined herein, all other technical and scientific terms used herein have the meanings commonly understood by those skilled in the art to which the present invention belongs.
[0101] As used herein, the terms "comprise", "include", and "contain" are used interchangeably and include not only closed definitions, but also semi-closed and open definitions. In other words, the terms include "consisting of", "consisting essentially of".
[0102] As used herein, the terms "N-hydroxysuccinimide," "NHS," are used interchangeably.
[0103] As used herein, the terms "1-ethyl-3-(3-dimethylaminopropyl)carbodiimide," "EDC," are used interchangeably.
[0104] As used herein, the terms "acrylic acid-N-hydroxysuccinimide ester", "AAc-NHS" are used interchangeably.
[0105] As used herein, the terms "liquid metal", "LM" are used interchangeably.
[0106] As used herein, the terms "phosphate buffered saline," "PBS," are used interchangeably.
[0107] As used herein, the terms "cystamine dihydrochloride," "Cys," are used interchangeably.
[0108] As used herein, the terms "reversibly adhesive polyelectrolyte hydrogel," "BPA," are used interchangeably.
[0109] As used herein, the terms "reversibly adhesive polyelectrolyte hydrogel electronic interface material," "BPAIE," are used interchangeably.
[0110] Polyampholyte hydrogel
[0111] As used herein, polyampholyte (PA) hydrogel refers to a hydrogel network comprising anionic monomers and cationic monomers that exhibits mild swelling behavior after dialysis in water.
[0112] Representatively, such as Figure 1 As shown, the anionic monomer used in the present invention is sodium p-styrene sulfonate (NaSS), and the cationic monomer is quaternized N,N-dimethylaminoethyl acrylate (DMAEA-Q) with methyl chloride.
[0113] Amino-functionalized hydrogel
[0114] As used herein, amino-functionalized hydrogel refers to a polymer hydrogel obtained by grafting the disulfide bonds of cystamine dihydrochloride onto a hydrophilic hydrogel.
[0115] Preferably, the amino-functionalized hydrogel of the present invention has the structural formula XSS-NH 2 , wherein X is hyaluronic acid, -SS- is a disulfide bond. 2 It is beneficial for the hydrogel to rapidly adhere to tissues, and the presence of disulfide bonds enables the hydrogel to be detached from the tissue surface without trauma in the presence of a separation solution.
[0116] Liquid metal coating
[0117] The liquid metal coating used in the present invention is a gallium-indium alloy (EGaIn) liquid metal coating. EGaIn is a liquid metal with a melting point close to or lower than room temperature. It has excellent properties such as fluidity, high conductivity, thermal conductivity, stretchability, self-healing ability, biocompatibility and recyclability. These properties of EGaIn can be adjusted by changing the experimental conditions, and EGaIn can be mixed with other materials to further obtain composite materials with various extended properties.
[0118] BPAIE
[0119] The BPAIE of the present invention refers to a reversibly adhesive polyelectrolyte hydrogel (BPA) having high mechanical and tissue adaptability, reversible adhesion, anti-swelling, anti-fatigue and other properties formed by combining a polyampholyte network and an amino-functionalized hydrogel network. Subsequently, a metal coating is printed on the BPA to form a BPAIE with conductive properties.
[0120] Typically, the BPAIE of the present invention comprises the following components:
[0121] A. A polyampholyte (PA) formed by polymerization of anionic monomer NaSS and cationic monomer DMAEA-Q, wherein the molar ratio of NaSS to DMAEA-Q is 0.52:0.48, and the PA solution also includes a component MBAA and a component α-ketone, each of which has a content of 0.1 mol%, and the total ionic monomer concentration of the PA solution is Cm=2.0 M;
[0122] B. hyaluronic acid grafted with amino functional groups (HA-Cys), wherein HA-Cys accounts for 1 wt % of BPA;
[0123] C. Gallium-indium liquid metal coating.
[0124] Preparation method
[0125] The preparation method described in the present invention refers to the preparation method of BPA or BPAIE.
[0126] Typically, the preparation method of the present invention comprises the following steps:
[0127] Z1: 1.00 g sodium hyaluronate, EDC (0.05 mol / L) and NHS (0.05 mol / L) were dissolved in 450 mL PBS solution to form a mixed solution, and then 0.842 g Cys was added to the mixed solution and stirred overnight to form a HA-Cys solution;
[0128] Z2: NaSS and DMAEA-Q in a molar ratio of 0.52:0.48, MBAA in a content of 0.1 mol% and α-ketone were mixed to obtain a PA solution;
[0129] Z3: PA solution and HA-Cys were mixed to obtain a uniform solution, in which HA-Cys accounted for 1wt%, and then the uniform solution was transferred to a sealed glass bottle and UV cross-linked for 11h to polymerize the hydrogel. Finally, the prepared hydrogel was immersed in a large amount of water for 1 week to allow the gel to swell and balance and wash away the residual chemicals to form the final sample.
[0130] Preferably, the preparation method further comprises adding a conductive material to the surface of BPA to form BPAIE, for example, printing a gallium-indium liquid metal coating on the surface of BPA.
[0131] Compared with the prior art, the advantages of the present invention are as follows:
[0132] 1. Reversible adhesion: The amino groups on the backbone of the BPAIE of the present invention can form stable crosslinks with the carboxylic acid groups on the tissue surface within a few minutes; in the presence of a separation solution, the disulfide bonds are broken, and the BPAIE of the present invention can be peeled off from the tissue surface without trauma.
[0133] 2. Anti-fatigue: The BPAIE of the present invention has a dynamic multiphase network with high fatigue resistance and self-recovery ability by breaking and rebonding ionic bonds during periodic heartbeats.
[0134] 3. Anti-swelling: The combination of the hydrophilic amino-functionalized hyaluronic acid network and the controlled swelling polyampholyte network enables the BPAIE of the present invention to have moderate water absorption and swelling capabilities.
[0135] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are intended to illustrate the present invention only and are not intended to limit the scope of the present invention. The experimental methods in the following examples where specific conditions are not specified are usually performed under conventional conditions, such as those described in Sambrook et al., Molecular Cloning: A Laboratory Manual (New York: Cold Spring Harbor Laboratory Press, 1989), or under conditions recommended by the manufacturer. Unless otherwise indicated, percentages and parts are weight percentages and weight parts.
[0136] Materials and Methods
[0137] 1. Experimental Materials
[0138] Cationic monomers methyl chloride quaternized N, N-dimethylaminoethyl acrylate (DMAEA-Q, 80% wt aqueous solution, Macklin), anionic monomers sodium p-styrene sulfonate (NaSS, Aladdin), sodium chloride (NaCl, Macklin), acrylic acid (AAc), acrylic acid-N-hydroxysuccinimide ester (AAc-NHS), N, N-methylenebis(acrylamide) (MBAA, Macklin) and hyaluronic acid (HA, Mw 400,000–800,000 Da, Macklin), sodium hyaluronate (22 × 105 Da, Macklin), α-ketoglutaric acid (α-keto, Macklin), cystamine dihydrochloride (Cys, Aladdin), N-hydroxysuccinimide (NHS, Aladdin), 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC, Aladdin), and all porcine tissues were purchased from local markets.
[0139] 2. Experimental Methods
[0140] Mechanical testing
[0141] The tensile stress-strain curves of the adhesive hydrogels were analyzed using a mechanical testing machine with a 20 N load cell. The tensile specimens were in a dumbbell shape with dimensions of 2 mm × 12 mm × 1 mm and then stretched at a strain rate of 50 mm / min. From the load-displacement curves, the fracture toughness was calculated.
[0142] Swelling test
[0143] To measure the swelling behavior of hydrogels with different compositions, the samples were immersed in various liquids and then weighed periodically. The swelling ratio of the hydrogel was then calculated using the following formula: Swelling ratio = (W t -W 0 ) / W 0 × 100%, where Wt is the weight after swelling and W0 is the original weight of the hydrogel.
[0144] Electrical testing
[0145] The real-time resistance (R) of sample 1 was recorded by an ohmmeter (GOM-804) with a high scanning frequency controlled by a LabView program. For the cyclic test, the resistance was measured at 0% and 30% strain and repeated for 1,000 cycles at a rate of 50 mm / min.
[0146] In vitro tissue adhesion assay
[0147] The interface toughness was tested by a 180° peel test using a mechanical testing machine SANS CMT2503, where a 10 mm wide sample was compressed on the heart tissue. The lap shear strength was tested by a lap shear test, where a 15×15 mm 2 The tensile strength was tested by tensile test. A 15×15 mm 2 The area of the substrate was fixed to the heart tissue and compressed. The bonding strength was applied to the terminals of the substrate at a rate of 50 mm / min using a 20N load cell.
[0148] Example 1. Sample preparation
[0149] Preparation of amino-functionalized hyaluronic acid monomer (HA-Cys)
[0150] In order to disulfide-graft cysteamine dihydrochloride (Cys) onto HA, 1.00 g of sodium hyaluronate, EDC (0.05 mol / L) and NHS (0.05 mol / L) were dissolved in 450 mL of PBS solution, and then 0.842 g of Cys was added to the sodium hyaluronate solution, and stirring was continued overnight to form a HA-Cys solution.
[0151] Preparation of polyampholyte (PA) hydrogel
[0152] PA hydrogel (P(NaSS-co-DMAEA-Q)) was synthesized by free radical copolymerization. The total ionic monomer concentration was Cm = 2.0 M, the molar ratio of NaSS to DMAEA-Q was 0.52:0.48, and the MBAA and α-ketone contents were both 0.1 mol% (relative to the total monomer concentration relative to the concentration of Cm) to obtain a PA solution. The homogeneous solution was transferred to a sealed glass bottle and irradiated with ultraviolet light to initiate polymerization (11 hours) until polymerization. Then, the prepared hydrogel was immersed in a large amount of water for 1 week to allow the gel to equilibrate and wash away residual chemicals to form a PA hydrogel.
[0153] Preparation of NHS ester functionalized hyaluronic acid monomer (HA-NHS)
[0154] Grafting of NHS ester functionalized monomers onto HA (HA-NHS) HA (1% w / w), EDC (0.05 mol / L) and NHS (0.05 mol / L) powders were completely dissolved in deionized water at pH 5. HA-NHS solution was obtained by stirring the mixture at room temperature.
[0155] Preparation of hydrogel sample 1
[0156] PA solution and HA-Cys were mixed to obtain a uniform solution. HA-Cys was prepared in different ratios to adjust the desired properties (0.5wt%, 1wt%, 2wt%). The uniform solution was transferred to a sealed glass bottle and UV cross-linked and cured for 11h. Then, the prepared hydrogel was immersed in a large amount of water for 1 week to allow the gel to swell and wash away the residual chemicals to form the final sample.
[0157] Sample 1 is the BPA of the present invention, wherein the proportion of HA-Cys is 1 wt %.
[0158] The proportions of HA-Cys in sample 1-0.5, sample 1-1, and sample 1-2 are 0.5wt%, 1wt%, and 2wt%, respectively.
[0159] Preparation of hydrogel sample 2
[0160] PA solution and HA-NHS (1 wt%) were mixed to obtain a uniform solution. The uniform solution was transferred to a sealed glass bottle and irradiated with ultraviolet light to initiate the polymerization reaction (11 hours). Then, the prepared hydrogel was immersed in a large amount of water for 1 week to allow the gel to reach equilibrium and wash away the residual chemicals to form sample 2 hydrogel.
[0161] Preparation of hydrogel sample 3
[0162] An acrylic acid mixed solution (30% w / w AAc, 0.03% w / w MBAA and 0.15% w / w 2,2′-azobis(2-methylpropionamidine) dihydrochloride) was dissolved in deionized water and 1% AA-NHS monomer and sealed and heated at 70° C. for 30 minutes to form a sample 3 hydrogel.
[0163] Preparation of hydrogel samples 4
[0164] An acrylic acid mixed solution (30% w / w AAc, 0.03% w / w MBAA, and 0.15% w / w 2,2′-azobis(2-methylpropionamidine) dihydrochloride) was dissolved in deionized water, and 1% HA-Cys monomer was sealed and heated at 70° C. for 30 min to form a sample 4 hydrogel.
[0165] Preparation of printable gallium indium liquid metal (EGaIn LM) ink
[0166] 0.5 g PVP (polyvinyl pyrrolidone, Mn (molecular weight) = 1,300,000, Aladdin, China) was added to 9.5 g hexanol (98%, McLean, China) and stirred for 48 hours to obtain a PVP solution. 4 g liquid metal (gallium indium alloy, Ga: In = 4: 1, Hawk, HK3284, China) was added to 1 ml PVP solution to obtain EGaIn LM ink. Ultrasonic treatment was performed for 60 seconds with an amplitude of 20% (5 seconds on and 10 seconds off) using a probe sonicator. The EGaln / PVP solution was then dried under high vacuum to remove the solvent. The EGaln ink was pre-pressed and printed directly on the BPAIE surface.
[0167] Fabrication of reversibly adhesive polyelectrolyte hydrogel electronic-tissue interface (BPAIE)
[0168] The sample 1 hydrogel was air-dried at room temperature for 12 h to prepare the BPAIE and used in a dry state to promote wet adhesion. A customized mask was placed on the surface of the sample 1 dry film and immediately fixed to the film surface. The conductive pre-pressed liquid metal ink was then transferred to the mask. Subsequently, the mask was removed to create a specific pattern. Finally, the liquid metal pattern and the wire were encapsulated together to form the BPAIE. The BPAIE was used with cardiac tissue wiped with a primer. The primer mainly consisted of EDC, 0.5wt%; NHS, 0.5wt%.
[0169] Example 2. BPAIE has anti-fatigue properties
[0170] To achieve a highly mechanically and tissue-adaptable bioelectronic interface, a tough polyampholyte (PA) network consisting of oppositely charged anionic monomers NaSS and cationic monomers DMAEA-Q ( Figure 1 Left) Random copolymerization at the charge balance point, showing a dynamic multiphase network structure (i.e., chemical network and physical network) after dialysis in water ( Figure 2 ). The dynamic multiphase network endows the PA with high fatigue resistance and self-recovery ability by breaking and rebonding ionic bonds during periodic heartbeats.
[0171] Example 3. Successful introduction of disulfide bonds by BPAIE
[0172] To achieve immediate and tenacious adhesion to cardiac tissue, the amino groups on the HA-Cys backbone can form stable crosslinks (i.e., amide bonds) with the carboxylic acid groups on the tissue surface within a few minutes by using primers and HA-Cys in BPAIE. The primers on the tissue surface are composed of EDCN-hydroxysuccinimide NHS. Inspired by the spatial structure of the polypeptide chain that is disconnected by disulfide bonds in the receptor, dihydrochloride (Cys) disulfide bonds are introduced to modify hyaluronic acid (HA-Cys), allowing BPA-NH2 to form dynamic adhesion bonds with tissues.
[0173] The proton nuclear magnetic resonance (1H NMR) spectrum of HA-cys is shown in Figure 3 As shown, it indicates that disulfide bonds were successfully introduced into the hydrogel.
[0174] Example 4. BPAIE has anti-swelling properties
[0175] Excessive swelling of the hydrogel can lead to strain mismatch between the device-tissue interface, which can weaken the adhesion of the electrode. When the reversibly adhesive polyelectrolyte hydrogel electronic-tissue interface comes into contact with the tissue surface, the sample 1 network begins to absorb and remove water from the tissue surface.
[0176] First, the water absorption and swelling behavior of sample 1 were investigated ( Figure 4 ). After soaking in PBS solution, the mass of sample 1 increased by about 20% after 2 minutes due to rapid water absorption, followed by slow absorption over the next 1000 minutes. In contrast, the mixture of the more hydrophilic amino-functionalized HA network and the more hydrophobic PA network gave sample 1 moderate water absorption and swelling, which was better than the more hydrophilic acrylic-based adhesive samples 3 and 4 and the more hydrophobic sample 2. The water absorption behavior of these PA network polymers is much milder than that of polyacrylic acid-based adhesives ( Figure 4 b), which may be due to the electrostatic attraction between PA polymer chains.
[0177] The results show that sample 1 has moderate water absorption capacity, which is beneficial to the mechanical and tissue adaptability of the reversibly adhesive polyelectrolyte hydrogel electronic tissue interface.
[0178] Example 5. BPAIE has mechanical and conductive stability
[0179] Sample 1 / The mechanical and conductive stability of the liquid metal composite when matched to repetitive heartbeats can reduce chronic fatigue of cardiac tissue.
[0180] Firstly, the cyclic behavior of sample 1 was studied by cyclic loading-unloading tensile test ( Figure 5). During the 10 consecutive cycles of loading-unloading tensile test at 100% strain, due to the internal fracture caused by the debonding of dynamic ions, it can be observed that the dissipated energy decreases slightly with the increase in the number of cycles until the dissipated energy and dissipation efficiency tend to a steady state due to the dynamic balance between fracture and reformation.
[0181] The results show that two parameters are used to quantify fatigue resistance in cyclic tests: energy dissipation index and residual strain. They reflect the effective energy dissipation and gradual stabilization during repeated heartbeats. The energy dissipation index (area of any loading curve in the stress-strain curve / area of the first loading curve) decreases at the beginning of the cycle due to polymer network rearrangement and initial ionic bond rupture.
[0182] As the cycle continues, the energy dissipation index can reach a stable state, which is due to the dynamic balance between ionic bond breaking and reconstruction in the rearranged polymer network. The residual strain is opposite to the trend of the energy dissipation index, increasing significantly at first and stabilizing at around 40-50% after 100 cycles, indicating the adaptability of the hydrogel structure to cyclic stress.
[0183] Next, the fracture behaviors of the unnotched and notched composite samples were studied separately.
[0184] The results show that the fracture energy of sample 1 is more than 7 times that of sample 3, and it is not easy to break in actual use because sample 1 can effectively dissipate mechanical energy, thereby preventing cracks from extending through reversible fracture and reformation of non-covalent interactions ( Figure 6 ). This ideal efficient energy dissipation, self-recovery, and fatigue resistance help to stably maintain the electrical cycling characteristics of Sample 1.
[0185] In terms of electrical properties, BPAIE exhibits stable electrical conductivity ( Figure 7 ).
[0186] Example 6. BPAIE has good tissue adhesion
[0187] Once in contact with a moist tissue surface, the moderate hygroscopicity of the HA-Cys network in sample 1 promotes rapid absorption and removal of interfacial water and forms immediate physical crosslinks (i.e., hydrogen bonds) with the tissue surface. In addition, by using primers, the amine groups on the HA-Cys backbone can form stable crosslinks (i.e., amide bonds) with the carboxylic acid groups on the tissue surface within a few minutes. To characterize the adhesion ability and compliance of the electrodes, the tissue adhesion of bioadhesive polymers was intensively studied in various simulations due to the moist and dynamic physiological environment during cardiovascular expansion and contraction.
[0188] To evaluate the tissue adhesion strength of sample 1 with different HA-Cys ratios on the cardiac tissue surface, a 180° peel test, lap shear test, and tensile adhesion strength ( Figure 8 ad). Sample 1 was first pressed gently onto the wet tissue for 10 seconds and then tested after 5 minutes to form a stable adhesion interface.
[0189] The results showed that the strong adhesion strength was due to the appropriate water absorption capacity, tough network and energy dissipation, and the subsequent formation of multiple adhesion mechanisms. Compared with the pure PA film, the sample 1 patch showed stronger and tougher adhesion, with more than 3.5 times higher interface toughness, 4 times higher shear strength, and 2 times higher tensile adhesion strength, indicating that HA-Cys plays a key role in the adhesion performance of the sample 1 patch.
[0190] Example 7. BPAIE has triggerable separation
[0191] The need for triggerable detachment of bioelectronic tissue interfaces may exist over a wide range of timescales, including intraoperative repositioning, removal within minutes to hours, or removal days to weeks after device implantation. Therefore, bioadhesive agents should be able to provide triggerable detachment in an effective and biocompatible manner over a wide range of timescales.
[0192] To cleave the physical crosslinks, sodium chloride-derived sodium cations were used to neutralize the negatively charged carboxylate groups. To cleave the covalent crosslinks, cleavable disulfide bonds were introduced between the amine groups and the HA network by synthesizing the functional monomer HA-Cys, thereby further weakening the adhesion and enabling on-demand and benign detachment. Here, BPAIE was stripped on-demand using a biocompatible detachment solution containing sodium chloride and glutathione (GSH) solution. ( Figure 8 g).
[0193] In situ validation of adhesion and detachment functions, BPAIE exhibited immediate and strong adhesion to the surface of rat heart and synchronous movement with the surface of rat heart. Subsequently, benign detachment was achieved using detachment solution without damaging the tissue ( Figure 8 e).
[0194] To verify the triggerable cleavage of physical and covalent cross-links of sample 1 by the separation solution, a carboxylic acid-bearing fluorescent group was used as a model to evaluate the adhesion and detachment of sample 1 to biological tissue surfaces ( Figure 8 f).
[0195] The results showed that sample 1 incubated with the fluorophore in PBS for 30 minutes showed a significant difference compared with the PA patch without HA-cys ( Figure 8 fi), sample 1 stably adheres to the fluorophore ( Figure 8f ii). Sample 1 was further incubated with the fluorophore in PBS and 0.5 M sodium chloride solution ( Figure 8 f iii), and incubate PBS with the separation solution for 5 min ( Figure 8 f iv). In contrast, in PBS with separation solution, sample 1 was almost completely separated from the fluorophore.
[0196] To investigate the effect of the triggerable separation mechanism on the adhesion performance, the interfacial toughness ( Figure 8 h).
[0197] The results show that the interface toughness decreased from 285.8 to 41.4, indicating that the bioelectronic-tissue interface can be peeled off from the tissue surface without trauma. After 10 repeated adhesion peeling tests, the interface toughness of sample 1 remained at 125 J m -2 This ensures adhesion after a single break in the bioelectronic tissue interface.
[0198] The successful incorporation and separation of disulfide bonds in sample 1 were further verified by UV spectroscopy analysis. Dynamic disulfide bonds appeared in the initial sample 1 and remained after incubation in 0.5 M sodium chloride. At the same time, they disappeared after 5 minutes of incubation in the separation solution ( Figure 8 i).
[0199] The above results indicate that the attachment of carboxylic acid-rich fluorophores to sample 1 is stable and their complete triggered detachment requires the cleavage of both physical cross-links (via NaCl) and covalent cross-links (via GSH).
[0200] Example 8. BPAIE has good biocompatibility
[0201] The in vitro and in vivo cytocompatibility of reversibly adhesive polyelectrolyte hydrogel electronic-tissue interfaces was evaluated. Fig. 9 ).
[0202] The results showed that although liquid metal particles had biosafety issues, they did not cause any serious cytotoxicity due to the presence of the encapsulation layer, which was consistent with the cell viability and LIVE / DEAD staining results.
[0203] Example 9. In vivo bioelectronic interface capability testing of BPAIE
[0204] The preparation process of BPAIE is as follows ( Fig.10 ) and experimental methods, electrophysiological recordings were performed on rat hearts via BPAIE to demonstrate their in vivo bioelectronic interfacing capabilities ( Fig.11 ).
[0205] The results showed that the ECG signals recorded by the four sensing channels (called Ch1, Ch2, Ch3 and Ch4) of BPAIE attached to the cardiac tissue from the right ventricle to the left ventricle were analyzed. Each of the four channels showed a different shape of cardiac signals (P, Q, R, S and T peaks), indicating that the BPAIE patch remained in its original position on the dynamic tissue surface. In addition, BPAIE showed stable integration with the target tissue and accurate recording of ECG signals in a normal mouse model.
[0206] All documents mentioned in the present invention are cited as references in this application, just as each document is cited as reference individually. In addition, it should be understood that after reading the above teachings of the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.
Claims
1. A reversibly adhesive polyelectrolyte electronic interface material, characterized in that: The material includes the following components: (a) a polyampholyte network, wherein the polyampholyte network comprises an anionic monomer NaSS and a cationic monomer DMAEA-Q; (b) a hydrogel network grafted with amino functional groups, wherein the hydrogel network is polymerized from amino functional monomers and has a structural formula of XSS-NH2, Wherein, X is a hydrophilic hydrogel monomer, -SS- is a disulfide bond, and -NH2 is an amino functional group; and (c) Metal coating.
2. The interface material according to claim 1, characterized in that The (a) network and (b) network together form the bonding substrate.
3. The adhesive substrate according to claim 2, characterized in that In the adhesive substrate, the proportion of (b) is 0.1wt%-10wt%, preferably 0.5wt%-2wt%.
4. The interface material according to claim 1, characterized in that The hydrogel network grafted with amino functional groups has reversible adhesion.
5. The interface material according to claim 1, characterized in that The hydrogel network grafted with amino functional groups can break disulfide bonds in the presence of a separation solution and non-invasively detach from the surface of biological tissues.
6. The interface material according to claim 1, characterized in that The separation solution is a solution containing sodium chloride and glutathione.
7. A reversibly adhesive polyelectrolyte hydrogel, characterized in that: The hydrogel comprises the following components: (a) a polyampholyte network, wherein the polyampholyte network comprises an anionic monomer NaSS and a cationic monomer DMAEA-Q; and (b) a hydrogel network grafted with amino functional groups, wherein the hydrogel network is polymerized from amino functional monomers and has a structural formula of XSS-NH2, Wherein, X is a hydrophilic hydrogel monomer, -SS- is a disulfide bond, and -NH2 is an amino functional group.
8. A reversible adhesion hydrogel, characterized in that: The hydrogel is a network structure formed by polymerization of amino-functional monomers, and the structural formula of the monomers is XSS-NH2. Wherein, X is a hydrophilic hydrogel monomer, -SS- is a disulfide bond, and -NH2 is an amino functional group.
9. A method for preparing a reversibly adhesive biomaterial, characterized in that: The method comprises the following steps: (a) preparing a hydrogel monomer solution grafted with amino functional groups, wherein the monomer has a structural formula of XSS-NH2, Wherein, X is a hydrophilic hydrogel monomer, -SS- is a disulfide bond, and -NH2 is an amino functional group; (b) preparing a polyampholyte solution; (c) (a) and (b) are mixed to obtain a reversibly adhesive biomaterial.
10. A use of a reversibly adhesive polyelectrolyte electronic interface material, characterized in that: Used to detect electrical signals on uneven biological tissue surfaces.